2016
DOI: 10.1016/j.hpb.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Defining post-operative pancreatitis as a new pancreatic specific complication following pancreatic resection

Abstract: Post-operative pancreatitis should be recognised as a separate pancreatic specific complication following pancreatic resection. Improved recognition may allow better understanding of potential methods of prevention, treatment and prediction of severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
142
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(154 citation statements)
references
References 45 publications
(97 reference statements)
1
142
0
1
Order By: Relevance
“…In addition, impaired blood perfusion and disruption of the gland remnant by surgical trauma have an important negative impact on the healing of a pancreatic anastomosis. Although some studies have shown that ensuring an adequate blood supply to the pancreatic remnant is essential for uneventful anastomotic healing, there is currently no general agreement about any standardized assessment of pancreatic remnant blood perfusion and postoperative pancreatitis. In the present study, the decision to recut the surface after initial pancreatic transection was based on the result of frozen‐section analysis and the individual surgeon's assessment of the remaining pancreatic tissue, but without objective evaluation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, impaired blood perfusion and disruption of the gland remnant by surgical trauma have an important negative impact on the healing of a pancreatic anastomosis. Although some studies have shown that ensuring an adequate blood supply to the pancreatic remnant is essential for uneventful anastomotic healing, there is currently no general agreement about any standardized assessment of pancreatic remnant blood perfusion and postoperative pancreatitis. In the present study, the decision to recut the surface after initial pancreatic transection was based on the result of frozen‐section analysis and the individual surgeon's assessment of the remaining pancreatic tissue, but without objective evaluation.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, there is growing evidence that POPFs have a complex aetiology, with postoperative pancreatitis and pancreatic necrosis as contributory factors. In addition, impaired blood perfusion and disruption of the gland remnant by surgical trauma have an important negative impact on the healing of a pancreatic anastomosis. Although some studies have shown that ensuring an adequate blood supply to the pancreatic remnant is essential for uneventful anastomotic healing, there is currently no general agreement about any standardized assessment of pancreatic remnant blood perfusion and postoperative pancreatitis.…”
Section: Discussionmentioning
confidence: 99%
“…While both markers on POD3 were strongly associated with CR-POPF in our cohort, their predictive value on POD1 was of borderline significance. The presence of POAP as defined by Connor [ 13 ] was only associated with further development of POPF when biochemical (not clinically relevant) leaks were included. This suggests a limited power in our cohort with a considerably low number of patients developing POAP (35.7%) compared to 55.8% in a previous Italian study involving 292 patients [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…POPF was defined according to the 2016 update of the International Study Group for Pancreatic Surgery (ISGPS), [ 10 ] postpancreatectomy haemorrhage (PPH) and delayed gastric emptying (DGE) according to the respective 2007 ISGPS definitions [ 11 , 12 ]. Post-operative pancreatitis (POAP) was defined by Connor’s proposal, with serum amylase/lipase values being increased above the upper limit of normal (53 and 60 U/L, respectively, according to our local laboratory) between surgery (skin closure) and end of POD1 [ 13 ]. Failure to rescue (FTR) was the rate of deaths in the total number of patients experiencing complications.…”
Section: Methodsmentioning
confidence: 99%
“…Postoperative acute pancreatitis (POAP) was defined as an elevation of amylase more than the upper limit of normal immediately after surgery or on post-operative day one. 13 Statistical analysis was performed with SPSS software (SPSS Inc., version 20 for Macintosh, IBM, Chicago, IL, USA). Continuous variables were expressed as the mean and SD or as the median with a range when appropriate.…”
Section: Methodsmentioning
confidence: 99%